(3GdMeGjI GdLfGFjI ddHjFI GdCQVjI e`f NW`Q GdehGO h GdfaGjGJ GdNWQI ai GdbGfhf GdeUQi (B/ s - (3eMeO UdGM YHOGdefYe MSjfs; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3EOQGkcG ef GdeTQY GdeUQi HGdCVQGQ h GdeNGWQ GdfGJLI Yf GdehGO h GdfaGjGJ GdNWQI(B: (3h GdJi JYJHQ ef Cge GdCSHGH GdJi JDOi Edi JdhK GdHjFI h JYQjV MjGI GdEfSGf h Cefg ddNWQ(B: (3abO MQU GdeTQY Ydi JLQje GdCaYGd GdJi JeKd GYJOGkA Ydi GdHjFI h GdEfSGf ef LQGA EOGQI h JOGhd GdehGO h GdfaGjGJ GdNWQI HGdeNGdaI ddbhGYO h GdGTJQGWGJ h GdELQGAGJ GdefUhU YdjgG HbGfhf GdHjFI h dGFMJg GdJfajPjI(B: (3h Pdc ef NdGd aQV YbhHGJ JOQLJ MSH NWhQI GdaYd eG Hjf YbhHI GdLfM h GdLfGjGJ(B: (3h jJe JTOjO gPg GdYbhHGJ EPG JQJH Ydi GdaYd GdeNGda MOhK YGgI eSJOjeI Ch haGI TNU Ch CcKQ(B: (3acGf GgJeGe GdeTQY HaQV MeGjI LfGFjI ddHjFI h GdEfSGf ef GdCVQGQ h GdeNGWQ GdeJQJHI Ydi GdehGO h GdfaGjGJ GdNWQ(B: (3fJjLI dEOQGcg deOi NWhQI gPg GdehGO h GdfaGjGJ Ydi GdHjFI h GdEfSGf; aEfg jfJL Yf JOGhd Ch EOGQI GdehGO h GdfaGjGJ GdNWQI Yf WQjb GSJNOGegG Ch fbdgG Ch JNRjfgG Ch JMQjcgG HWQjbI ZjQ Cefg h SdjeI HjFkjG(B: (3CVQGQ LSjeI HGdHjFI h GdEfSGfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B249-261s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMeGjI GdLfGFjIs; (3GdbGfhf GdeUQi s; (3GdfaGjGJ GdNWQI s; (3GdLQjeI GdHjFjIs; (3JOGhd GdehGO hGdfaGjGJ GdNWQIs; (3eNGdaI GOGQI GdfaGjGJs; (3GbGeI efTGI HZQV eYGdLI GdfaGjGJ GdNWQI HZjQ JQNjUs; (3LQjeI GSJjQGO GdfaGjGJ GdNWQIs; (3LQjeI GdSeGM HeQhQ GdSaf GdJi JMed GdfaGjGJ GdNWQIs; (3LQjeI YOe GdGMJaGX HSLd GdeNdaGJ GdNWQIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs